Cepharanthine synergizes with photodynamic therapy for boosting ROS-driven DNA damage and suppressing MTH1 as a potential anti-cancer strategy - Zi-Yi Yang; Liu-Gen Li; Yi-Lian Xiong; Nan-Nan Chen; Ting-Ting Yu; Hai-Tao Li; Tao Ren; Hui You; Xiao Wang; Tong-Fei Li; Mei-Fang Wang; Jun Hu (Photodiagnosis and Photodynamic Therapy)
Objective: Photodynamic therapy (PDT) primarily treats skin diseases or cancer by generating reactive oxygen species (ROS) to damage cellular DNA, yet drug resistance limits its application. To tackle this problem, the present study was carried out to improve the efficacy of chlorin e6 (Ce6)-PDT using Cepharanthine (CEP) as well as to reveal the potential molecular mechanism. Materials and methods: Lewis lung cancer cell line (LLC) was utilized as the cancer cell model. chlorin e6 (Ce6) acted as the photosensitizer to induce PDT. The in vitro anti-cancer efficacy was measured by CCK-8, Annexin-V/PI staining, and migration assay. The Ce6 uptake was observed using flow cytometry and confocal microscopy. The ROS generation was detected by the DCFH-DA probe. The analysis of MutT Homolog 1 (MTH1) expression, correlation, and prognosis in databases was conducted by bioinformatic. The MTH1 expression was detected through western blots (WB). DNA damage was assayed by WB, immunofluorescent staining, and comet assay. Results: Ce6-PDT showed robust resistance in lung cancer cells under certain conditions, as evidenced by the unchanged cell viability and apoptosis. The subsequent findings confirmed that the uptake of Ce6 and MTH1 expression was enhanced, but ROS generation with laser irradiation was not increased in LLC, which indicated that the ROS scavenge may be the critical reason for resistance. Surprisingly, bioinformatic and in vitro experiments identified that MTH1, which could prevent the DNA from damage of ROS, was highly expressed in lung cancer and thereby led to the poor prognosis and could be further up-regulated by Ce6 PDT. CEP exhibited a dose-dependent suppressive effect on the lung cancer cells. Further investigations presented that CEP treatment boosted ROS production, thereby resulting in DNA double-strand breakage (DDSB) with activation of MTH1, indicating that CEP facilitated Ce6-PDT-mediated DNA damage. Finally, the combination of CEP and Ce6-PDT exhibited prominent ROS accumulation, MTH1 inhibition, and anti-lung cancer efficacy, which had synergistic pro-DNA damage properties. Conclusion: Collectively, highly expressed MTH1 and the failure of ROS generation lead to PDT resistance in lung cancer cells. CEP facilitates ROS generation of PDT, thereby promoting vigorous DNA damage, inactivating MTH1, alleviating PDT resistance, and ameliorating the anti-cancer efficacy of Ce6-PDT, provides a novel approach for augmented PDT.